A Novel Hybrid Technique for Sub-pixel Edge Detection using Fuzzy Logic and Zernike Moment - Bala, Jyoti; Dhir, Renu Dhir (International Journal of Computer Sciences and Engineering, 2014)
This paper is based on the development of fuzzy Logic based edge detection techniques in digital images. The proposed technique used Sobel operator, Zernike moment operator, and Fuzzy inference system in combination for edge detection purpose. Edge is a boundary between two homogeneous regions. Edge detection refers to the process of identifying and locating sharp discontinuities in an image. In this paper, the main aim of edge detection technique is to filter out unnecessary, false and double edges in the final image.